Pengaruh Globalisasi Budaya Terhadap Penggunaan Bahasa Jawa Krama Mahasiswa PGMI Semester 5 UIN Sunan Ampel Surabaya - Khoiroh, Aifi Umdatul; Wardani, Federika Junia; Fauziah, Alifiah Restu (Prodi Pendidikan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2024)
Cultural globalization has changed communication patterns, especially among young people, by facilitating easier access to various information, including foreign languages. This research aims to determine the influence of cultural globalization on the use of the Javanese language and manners of PGMI Semester 5 students at UIN Sunan Ampel Surabaya. The method used is quantitative research with a survey research design. Data was collected using a questionnaire with a Likert scale, which had three categories: agree, disagree, and disagree. The research results show that the majority of PGMI Semester 5 students at UIN Sunan Ampel Surabaya who understand Javanese krama come from a solid Javanese cultural environment, such as Gresik, Lamongan, Ngawi, and Mojokerto, with a percentage showing a tendency to agree of 52.5%. However, in everyday life, these students do not agree with using Javanese manners, as evidenced by the percentage of students who disagree 42.5%, especially in a global environment, which is reflected in the percentage of those who are less confident in using the language, around 35%. From the results of this research, it can be concluded that globalization influences students' tendency to use Javanese manners, as shown by the high percentage of respondents who agree that globalization influences the use of this language, reaching 77.5%.